Self-association of supramolecular cages based on dynamic imine and β-diketone bonds - Kołodziejski, Michał (My University, 2025)
This doctoral dissertation presents research at the intersection of materials chemistry and fundamental supramolecular chemistry, conducted within two scientific pillars. The first pillar focused on the design and synthesis of functional materials based on β-diketone ligands, with an emphasis on their catalytic potential. A two-step synthesis was developed, which involved the preparation of dimeric palladium(II) metallocycles and their subsequent controlled polymerization. The resulting soluble metallosupramolecular polymer proved to be a significantly more efficient catalyst for the Suzuki-Miyaura coupling reaction compared to its cyclic precursor. The second pillar was devoted to investigating the fundamental principles of self-assembly and component sorting in the process of creating organic cages using Dynamic Covalent Chemistry (DCC). In a series of competitive experiments, extremely high selectivity was observed – the system spontaneously selected a single, most favored component for the construction of a homoleptic cage, never forming mixed products. A hierarchy of preferences was established and principles governing sorting were formulated. It was shown that these preferences result from the system reaching true thermodynamic equilibrium. The work comprehensively integrates materials chemistry with fundamental research. Rozprawa doktorska przedstawia badania z pogranicza chemii materiałowej i fundamentalnej chemii supramolekularnej, prowadzone w ramach dwóch filarów naukowych. Pierwszy filar koncentrował się na projektowaniu i syntezie funkcjonalnych materiałów opartych na ligandach β-diketonowych, z naciskiem na ich potencjał katalityczny. Opracowano dwuetapową syntezę, w której otrzymano dimeryczne metalocykle palladu(II), a następnie przeprowadzono ich kontrolowaną polimeryzację. Uzyskany rozpuszczalny polimer metalosupramolekularny, okazał się znacznie wydajniejszym katalizatorem w reakcji sprzęgania Suzuki-Miyaury, w porównaniu do jego cyklicznego prekursora. Drugi filar poświęcono badaniu fundamentalnych zasad samoorganizacji i sortowania komponentów w procesie tworzenia klatek organicznych przy użyciu Dynamicznej Chemii Kowalencyjnej (DCC). W serii eksperymentów konkurencyjnych zaobserwowano skrajnie wysoką selektywność – system spontanicznie wybierał jeden, najbardziej uprzywilejowany komponent do budowy homoleptycznej klatki, nigdy nie tworząc produktów mieszanych. Ustalono hierarchię preferencji i sformułowano zasady rządzące sortowaniem. Wykazano, że preferencje te wynikają z osiągania przez układ prawdziwej równowagi termodynamicznej. Praca kompleksowo łączy chemię materiałową z badaniami podstawowymi.
Samoasocjacja kapsuł supramolekularnych w opartych o dynamiczne wiązania iminowe oraz β-diketonowe
Wydział Chemii
Keywords: Supramolecular chemistry; Dynamic Combinatorial Chemistry; self-sorting; metallacycles; β-diketone ligands; Chemia supramolekularna; Dynamiczna Chemia Kombinatoryczna; samosortowanie; metalocykle; ligandy β-diketonowe